PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) PEGAWAI DI KANWIL PT. PEGADAIAN (PERSERO) JAWA TENGAH - Rosyada, Niya Farikha; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2016)
Organizational Citizenship Behavior (OCB) with regard to the manifestation of a person (employee) as a social creature. Emotional skills (ability to work) is part of the OCB to produce outstanding performance in the job. Organizational culture guide the behavior of employees to improve work ability, commitment and loyalty of employees who have the organizational commitment is high performing not only tasks that have become obligations, but will voluntarily work on things that can be classified as additional interventions (extra effort).Samples adalam this study are employees of PT. Pawnshop (Persero) Regional Office XI Semarang Pawnshop 60 people. Data collection techniques using a questionnaire with Likert scale. Test instruments used validity and test reliabiltas. Analysis of the data used is multiple linear regression, with ujit, F test and coefficient determinai.Based on the analysis and discussion of results, it can be concluded that (1) Cultural Organization positive and significant impact on the Organization Citizenship Behavior (OCB); (2) Organizational Commitment positive and significant impact on the Organization Citizenship Behavior (OCB) and (3) Organizational Culture and Organizational Commitment positive and significant impact on the Organization Citizenship Behavior (OCB).